Gender diversity for sustainability management: developing a research agenda from a supply chain perspective. Issue 3 (1st October 2020) - Ruel, Salomée; Fritz, Morgane; Subramanian, Nachiappan
ABSTRACT: Gender diversity (GD) is an issue that must be addressed for the sustainable development of businesses. Research is lacking on GD in the sustainability management of supply chains (SMSCs). This study addresses the potential impact of GD on SMSCs. A literature review methodology is used to review academic and professional articles over three decades. The findings show that some studies have examined GD and supply chain management (SCM) but the focus has tended to be on the challenges encountered by women in SCs, such as women as victims, but not women as potential change actors. In contrast, sustainability management literature invokes the importance of GD and the specificities women managers can bring to firms' performance. A research agenda is proposed in this study by combining outcomes from both fields. It implies there is an important space to fill, especially concerning the environmental and social impacts GD may have on SMSCs.